Framing and use of sources in media surveillance. Analysis of the Argentine and Chilean press: José López and Caval cases - Tagle, Francisco Javier; Claro, Cecilia (Estudios sobre el Mensaje Periodístico, 2018)
Among the functions expected of the media in democracies is to be vigilant of power. However, this normative ideal must be contrasted with reality, given that media outlets against political corruption use certain frames and select particular types of sources to construct the stories. All this, taking into consideration, that the Latin American media systems, which is where this study is inserted, are characterized, among other aspects, by a low pluralism, which can hinder an adequate information treatment. Through the cases of José López in Argentina and Caval in Chile, it is tried to evaluate, respectively, the surveillance role that the Clarín and La Nación newspapers and El Mercurio de Santiago and La Tercera had in their coverage. In this way, two categories of analysis are proposed that are considered fundamental when studying this media function for regional democracies: Frames and sources.